2017
DOI: 10.7755/fb.115.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Management strategy evaluation for the Atlantic surfclam (Spisula solidissima) using a spatially explicit, vessel-based fisheries model

Abstract: Abstract-The commercially valuable Atlantic surfclam (Spisula solidissima) is harvested along the northeastern continental shelf of the United States. Its range has contracted and shifted north, driven by warmer bottom water temperatures. Declining landings per unit of effort (LPUE) in the Mid-Atlantic Bight (MAB) is one result. Declining stock abundance and LPUE suggest that overfishing may be occurring off New Jersey. A management strategy evaluation (MSE) for the Atlantic surfclam is implemented to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Details of the SEFES model framework are provided by Munroe et al (2022), andScheld et al (2022) provide details of the economic analyses used to assess the fishing fleet and processor operations. Previous implementations of SEFES were used to evaluate temperature-induced range shifts in Atlantic surfclam distribution and associated effects on the stock, fishery, and management (Powell et al 2015Kuykendall et al 2017Kuykendall et al , 2019Stromp et al 2023, this themed issue). Assessment of the skill of simulations implemented with SEFES using a variety of fisheryindependent and fishery-dependent data showed that the model provides a reasonable representation of the existing fishery (e.g., Munroe et al 2022).…”
Section: Model Overviewmentioning
confidence: 99%
“…Details of the SEFES model framework are provided by Munroe et al (2022), andScheld et al (2022) provide details of the economic analyses used to assess the fishing fleet and processor operations. Previous implementations of SEFES were used to evaluate temperature-induced range shifts in Atlantic surfclam distribution and associated effects on the stock, fishery, and management (Powell et al 2015Kuykendall et al 2017Kuykendall et al , 2019Stromp et al 2023, this themed issue). Assessment of the skill of simulations implemented with SEFES using a variety of fisheryindependent and fishery-dependent data showed that the model provides a reasonable representation of the existing fishery (e.g., Munroe et al 2022).…”
Section: Model Overviewmentioning
confidence: 99%
“…The surfclam MSE allows evaluation of alternative management strategies that simultaneously address the two primary challenges facing sustainability of the surfclam stock and fishery: range contraction limiting stock abundance and a decline in the number and density of dense surfclam patches limiting the fishery. Simulations that implemented rotating closures as a management tool, based on the success of this approach for sea scallops Placopecten magellanicus (Hart & Rago 2015), were used to evaluate the effects of closure durations from 3 to 7 years, criteria for identifying areas for closure based on the true abundance or the proportional abundance of small surfclams, and a range of definitions for a small surfclam based on the time required for growth to market size (120 mm) (Kuykendall et al 2017).…”
Section: Surfclam Fishery-social and Economic Inputsmentioning
confidence: 99%
“…In addition, closure of one 10-min square per year resulted in increased LPUE because the areas opened each year contained highdensity surfclam patches. Thus, area management based on time-limited closures enhanced the stock and improved the fishery (Kuykendall et al 2017).…”
Section: Surfclam Fishery-social and Economic Inputsmentioning
confidence: 99%
See 2 more Smart Citations